Effects of HMG-CoA Reductase Inhibitors (Statins) On Bone Mineral Density and Metabolism - Nehir Samancı; M. Can Öksüz; Nilüfer Balcı; Mehmet Arman (Galenos Yayinevi, 2004)
Hydroxy methylglutaryl coenzyme A reductase inhibitors (statins) have been shown to have effects on bone metabolism in laboratory studies. While early clinic studies have showed lower risk for osteoporotic fractures among statin users than nonusers, subsequent studies have found mixed results. The purpose of this study was to investigate the effects of statins on bone mineral density (BMD) and bone metabolism. Thirty-five consecutive postmenopausal hypercholesterolemic women who were treated for at least last 6 months with statins were included in the study. Seventy-five normocholesterolemic age-matched postmenopausal women were in the control group. Subjects with a history of any diseases and used drugs that may affect calcium or bone metabolism were excluded from the study. Age, associated illness, years since menopause, and body mass index (BMI) were obtained from all the patients including the control group. Besides, serum calcium, phosphate, alkaline phosphates, parathyroid hormone, 25 hydroxy D3, osteocalcin, and urinary calcium excretion were measured. BMD was measured by using dual-energy x-ray absorptiometry (DEXA) at femoral neck and 3rd lomber spine. Mean duration of statin use was 28.17±21.17 months. BMI was found to be statistically higher in statin users than nonusers (27.47±3.67kg/m2 and 25.46±3.91 kg/m2, respectively). The markers of bone metabolism used in the study were found to be similar between the groups. BMD was not different in statin users and nonusers at femoral neck and lomber spine. As conclusion, statin use did not affect BMD and bone metabolism in this study. In our opinion large randomised, controlled, prospective clinical trials are needed to accurately determine the role of statins in the treatment of osteoporosis.